ETHNOBOTANY OF THE DOLLU PLANT (Dodonaea Viscosa) BY THE LANI TRIBE IN MAKKI DISTRICT, LANNY JAYA DISTRICT - Inggrid Kailola (Sean Institute, 2023)
Data on the local wisdom of the Papuan community can be viewed in the use of various types of plants for food ingredients, medicines, equipment for traditional ceremonies, building materials and some others. The local community's knowledge about the use of plants called ethnobotany can be found in the Lani Tribe in Makki District, Lanny Jaya Regency. The research methods that were used are the observation method and interview method. The data obtained was analyzed descriptively. The results of this study revealed that the Dollu plant (Dodonaea Viscosa) is very significant for the Lani people. It is used to stop bleeding for postnatal mothers, to treat wounds, basic materials for making houses (Honai- Papuan Traditional house) and fences, materials for making torches, burning corpses, clan marriages and clamps. The influences of modernization and new religion exposures, caused the community to abandon this plant. Based on research on the phytochemicals of the Dodonaea Viscosa plant, it contains very useful ingredients for health.